Working Memory And Phonological Awareness In The Phonological Deviation - Vieira, Michele Gindri (2015)
This study investigated the performance of children with phonological disorders in the working memory skills and in the phonological awareness skills, which are parts of the phonological processing and, whether such skills are related to each other, to the chronological age and to the degree of the phonological deviation. The sample was composed of 28 children with phonological deviation, ranging from 4 years old to 6 years and 7 months old, illiterate, with a hypothesis of pre-syllabic writing and, it was divided into two groups as follows: one with 21 children with a more severe phonological deviation and the other with 7 children with a softer phonological deviation. Speech-language and hearing evaluations were undertaken in order to diagnose the phonological deviation along as phonological assessments to determine the phonological system and to rate the degree of the speech impairment through a qualitative analysis. The children’s performance in the working memory assessments was checked through the repetition of a sequence of four digits – to assess the central executive and the phonological memory and, the repetition of non-words task – to assess specifically the phonological memory, according to Baddeley and Hitch’s proposal (1974 apud GATHERCOLE; BADDELEY, 1993), revised by Baddeley (1986). The performance in the phonological awareness evaluation was also checked, including the syllabic and phonemic awareness. The results are as follows: 1) the sample has presented a lower performance in the phonological memory and phonological awareness when compared to the performance of children with normal phonological development as seen in further research conducted in Brazil by making use of similar assessment methods; 2) there has been a significant correlation between the repetition of non-words task and the syllable awareness; 3) there was a statistical correlation between age and the repetition of nonwords task and, a weak correlation between age and the digit repetitions and, between age and phonological awareness. Comparing the groups was found that the children with a more severe phonological deviation have performed lower in all the tasks when compared to the group of softer deviations and, such difference was significant in the total scores of the phonological and in the phonemic awareness. It concluded that the preschoolers with phonological deviation, when considered as a group and not individually, have presented worse performance in tasks of phonological awareness and phonological memory than groups of children with normal phonological development and, that such skills are correlated in a significant way. Children with more severe phonological deviation have presented worse performance than children with less speech impairments, with a statistical difference in the phonological awareness tasks.